Limited diagnostic possibilities for bloodstream infections with broad-range methods: A promising PCR/electrospray ionization-mass spectrometry platform is no longer available - Tkadlec, Jan; Bébrová, Eliška; Beroušek, Jan; Vymazal, Tomáš; Adámková, Jaroslava; Martínková, Vendula; Moser, Claus; Dragos, Florea; Dřevínek, Pavel (MicrobiologyOpen, 2020)
Fast and accurate detection of causative agents of bloodstream infections remains a challenge of today's microbiology. We compared the performance of cutting-edge technology based on polymerase chain reaction coupled with electrospray ionization-mass spectrometry (PCR/ESI-MS) with that of conventional broad-range 16S rRNA PCR and blood culture to address the current diagnostic possibilities for bloodstream infections. Of 160 blood samples tested, PCR/ESI-MS revealed clinically meaningful microbiological agents in 47 samples that were missed by conventional diagnostic approaches (29.4% of all analyzed samples). Notably, PCR/ESI-MS shortened the time to positivity of the blood culture-positive samples by an average of 34 hr. PCR/ESI-MS technology substantially improved current diagnostic tools and represented an opportunity to make bloodstream infections diagnostics sensitive, accurate, and timely with a broad spectrum of microorganisms covered.
Keywords: polymerázová řetězová reakce; hmotnostní spektrometrie s elektrosprejovou ionizací; bakteriemie; lidé; Microbiological Techniques; mikrobiologické techniky; Bacteremia; Spectrometry, Mass, Electrospray Ionization; Humans; Polymerase Chain Reaction